Hypoxia-Activated PI3K/Akt Inhibits Oxidative Stress via the Regulation of Reactive Oxygen Species in Human Dental Pulp Cells. (9th January 2019) - Liu, Fei; Huang, Xin; Luo, Zhenhua; He, Jingjun; Haider, Farhan; Song, Ci; Peng, Ling; Chen, Ting; Wu, Buling
Abstract : In order to use stem cells as a resource for tissue regeneration, it is necessary to induce expansion in vitro . However, during culture, stem cells often lose functional properties and become senescent. Increasing evidence indicates that hypoxic preconditioning with physiological oxygen concentration can maintain the functional properties of stem cells in vitro . The purpose of the current study was to test the hypothesis that hypoxic preconditioning with physiological oxygen concentration can maintain the functional properties of stem cells in culture by reducing oxidative stress. In vitro studies were performed in primary human dental pulp cells (hDPCs). Reduced levels of oxidative stress and increased cellular "stemness" in response to physiological hypoxia were dependent upon the expression of reactive oxygen species (ROS). Subsequently, RNA-sequencing analysis revealed the increased expression of phosphoinositide 3-kinase (PI3K)/Akt signaling in culture, a pathway which regulates oxidative stress. Furthermore, we found evidence that PI3K/Akt signaling might affect intracellular ROS production by negatively regulating expression of the downstream protein Forkhead Box Protein O1 (FOXO1) and Caspase 3. Collectively, our data show that the PI3K/Akt pathway is activated in response to hypoxia and inhibits oxidative stress in a ROS-dependent manner. This study identified redox-mediated hypoxic preconditioning regulatory mechanisms that may be significant for tissue regeneration.